Communicating local products on the web: a comparison between Italian and English-language blogs. (2015) - Scorrano, Paola; Fait, Monica; Rosato, Pierfelice; Gravili, Silvia
The web is increasingly ranged as one of the options available to agri-food small and medium-sized enterprises (SMEs) in order to face the challenge on how to provide personal taste experiences and manage differentiation in a global market. This research aims at analysing users' lexical choices in unstructured web sources, identifying the essential determinants in the local products web communication, while highlighting the latter's contribution to both consumer empowerment and SMEs' competitiveness. A content analysis of Italian and English-language agri-food blogs was done, in order to retrieve the most frequent concepts from and detect the language used in such sources, thus guiding SMEs in their market decisions. Managerial implications are discussed, due to the sector's role in the development of the whole Mediterranean area and its ability to gain local preservation and territorial sustainable development.